Analisis Faktor yang Mempengaruhi Prevalensi Swamedikasi Sebelum dan Selama Wabah Covid 19 Studi pada Tenaga Kefarmasian di Provinsi Jawa Tengah - Fildza Huwaina Fathnin; Arifin Santoso; Indriyati Hadi Sulistyaningrum; Rina Dwi Lestari (Universitas Muhammadiyah Surakarta, 2023)
The rate of self-medication among pharmacist is currently very high, which can lead treatment failure and even be dangerous. The purpose of this study was to determine the prevalence and factors related to self-medication before and during the COVID-19 outbreak by Health Workers in Central Java. The purpose of this study was to determine the prevalence and factors related to self-medication before and during the COVID-19 outbreak by pharmacists in Central Java. In addition, it also evaluates the prevalence of self-medication from the perspective of pharmacists before and during the COVID-19 outbreak, identifies general conditions of self-medication before and during the COVID-19 outbreak, investigates sociodemographic characteristics and health patterns related to self-medication by pharmacists in Java. Middle. This type of research is non-experimental using a cross-sectional design. The samples taken were pharmacist in Central Java. Sampling by snowball sampling method and obtained as many as 82 respondents. The results showed the factors that significantly influenced self-medication were age (p=0.05), the willingness or plans of the pharmacists themselves to carry out self-medication (p=0.000), pandemic conditions (p=0.023), and encouragement from other people (p=0.023). p=0.001). While the most dominating factor is the plan to continue self-medication (Sig.B=18.424).). There was a significant difference between the prevalence before and during the Covid-19 pandemic (p=0.007). The conclusion in this study is the Covid-19 pandemic has increased the prevalence rate of self-medication.